ChemInform Abstract: Enantioselective Desymmetrizations Promoted by Bifunctional Organocatalysts. Issue 18 (May 2015) - Quintavalla, Arianna; Cerisoli, Lucia; Montroni, Elisa
Abstract Review: 214 refs.